1991
DOI: 10.4278/0890-1171-5.3.215
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sociodemographic Characteristics and Recruitment, Retention, and Health Improvements in a Worksite Health Promotion Program

Abstract: Data suggest demographic characteristics are related to recruitment and retention in a health promotion program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Taken together, these data highlight opportunities to intervene upon Blacks recognition of the health consequences of overweight. Given that weight management interventions have shown very limited success among US Blacks [39][40][41][42][43][44][45][46], these preliminary findings suggest that some paradigm shifts may be necessary in our understanding of Blacks' views about weight in order to better intervene.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these data highlight opportunities to intervene upon Blacks recognition of the health consequences of overweight. Given that weight management interventions have shown very limited success among US Blacks [39][40][41][42][43][44][45][46], these preliminary findings suggest that some paradigm shifts may be necessary in our understanding of Blacks' views about weight in order to better intervene.…”
Section: Discussionmentioning
confidence: 97%
“…CONCLUSIONS-Because clinicbased programs may not reach minorities and may not be successful with those they do reach (3,24), programs that are community based have become increasingly popular as a means of delivering health education programs to minorities (25). Along with this trend is the practice of making use of educators who are members of the community in which the intervention is delivered (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Center for Health Statistics, 48% of African-American women between the ages of 20 and 74 are overweight, compared with 32% of white women of the same age-group (1). Although as many black women as white women report that they are dieting to lose weight (2), fewer black women enroll in weight loss programs (3). Further, when African-American women enroll in weight loss programs, they appear less likely to benefit than white women.…”
mentioning
confidence: 95%
“…This racial difference in attrition rates among families may parallel the relative high attrition rates (Bril et al, 1991) and poorer treatment outcomes observed among adult minority individuals in obesity treatment programs. The differential attrition rate suggests the need for specific strategies designed to engage and treat minority populations (Kumanyika et al, 1991;McGinnis, Ballard-Barbash, 1991).…”
Section: Discussionmentioning
confidence: 99%